Developing Children's Social Skills Through Traditional Games (A Case Study on Children Aged 4-6 Years in Developing Social Skills at ABA 1 Kindergarten, Sukabumi City) - Ibnu Hurri; Redi Awal Maulana; Elnawati Elnawati; Ira Maya Maspupah (STKIP Singkawang, 2006)
This study aims to examine the impact of traditional games on the development of social skills in children aged 4–6 years at Aisyiyah Bustanul Athfal (ABA) 1 Kindergarten in Sukabumi City. This study used a qualitative methodology with a case study design. This study included 17 children aged 4-6 years who were actively engaged in learning activities centered on local content. Data collection was conducted through participant observation, teacher interviews, and documentation of educational activities. The analysis involved the triangulation of sources and methodologies to guarantee the validity of the data. The study findings indicate that the traditional game of engklek significantly improves the social skills of children aged 4–6 years at Aisyiyah Bustanul Athfal (ABA) 1 Kindergarten in Sukabumi City. Children demonstrated improvements in collaboration, communication, empathy, turn-taking, adherence to game rules, and conflict resolution. Furthermore, hopscotch encouraged active participation, cooperative behavior, and improved social relationships among peers. These findings confirm that integrating traditional games into early childhood education preserves local culture and effectively enhances the development of social skills in early childhood.